Everyday stories of home: investigating experiences of the global financial crisis (2008) for British expatriates in the Costa del Sol - Miller, Rebekah (The University of Edinburgh, 2015)
This ethnographic research focuses on the experiences, and concept, of home for British expatriates in the Costa del Sol. By focusing on British expatriates, this thesis contributes to the under-theorised concept of home within transnational migration literature. I argues that home is a non-linear process, which includes its making, remaking and unmaking. Within this thesis, home is used as a lens through which the impacts of the global financial crisis (2008) for British expatriates in the Costa del Sol can be understood. These everyday impacts, and concepts of home, are presented through three individual stories. Such an in-depth approach contributes to traditionally more synoptic understandings of the financial crisis (see Harvey, 2010a; Aalbers, 2009). By providing details about the practices, material objects, relationships, emotions and processes linked to their sense of home, this research demonstrates the ‘messiness’ of everyday life (Highmore, 2002; Law, 2004). They are stories of hardship, precariousness, and of getting by. They are also stories of re-imagining aspirations, expectations, and identity.
Keywords: transnational migration; lifestyle; financial crisis; narrative; home; everyday; MSc Human Geography